Peningkatan Pelayanan di Poli Kebidanan dan Kandungan RSUD Saiful Anwar dengan Menggunakan Simulasi Antrian - Mas'udin, Ilyas (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This research have aim to reduce waiting time of patient in pregnant division at RSUD Saiful Anwar Malang. First step, collecting the time between arrival data and service time data at each division. These data were tested using Kolmogorov-Smirnov to find a kind of distribution and the parameter of the data. Them making service system design based on the initial condition using ARENA and run to find the mean of waiting time from the beginning design, using trial and error then tried some new altematives design to minimize waiting time.